Guiding organizations in the digital era: Tools and metrics for success - Italo C Fantozzi; Jan Olhager; Charlotta Johnsson; Massimiliano M Schiraldi (International Journal of Engineering Business Management)
This study develops a strategic framework to guide the adoption of Industry 4.0 technologies across various business sectors. Using a mixed-methods approach, the research combines an extensive literature review with empirical investigations, including case studies and surveys with industry practitioners. The framework integrates advanced digital technologies, such as artificial intelligence and immersive solutions, and provides specific indicators to measure adoption progress. Key findings highlight critical business areas benefiting from digital transformation, such as production, operations management, and IT, showcasing improvements in resource management, operational efficiency, and innovation capabilities. The study’s originality lies in its comprehensive and actionable framework, validated through empirical data and aligned with international standards, offering practical tools for businesses navigating digital transformation.